The only saloon in town [large type] - Wortham, Reavis Z. (Wortham, Reavis Z. Cap Whitlatch western, 2025)
"A couple stiff drinks after a long day's ride. That's all Cap Whitlatch and his one-armed buddy Gil are looking for when they drift into the dusty town of Angel Fire. Problem is, there's only one saloon and they don't accept U.S. currency. Just gold and silver coins. Which means Cap and Gil have to go to the only bank in town to exchange their bills for coins. Unfortunately for them, the bank is about to get robbed by the wildest sons-of-guns this side of the Rio Grande . . . It turns out Cap and Gil aren't the only ones who need the gold and silver to get a drink. There's a rowdy crew of rough riders from the north, ranch hands from Panther Creek, and a vicious bunch of scalp hunters with a grisly cargo of Commanche and Apache scalps. Since the bank president is out of town, the teller can't exchange anyone's money. Which doesn't sit well with some of the boys, who decide to take the gold and silver themselves with bullets and bloodshed as collateral. Things turn ugly fast. The town marshal turns his head. Which leaves Cap and Gil to deal with these marauding devils before they blow the whole town of Angel Fire to kingdom come . . ."--